Red Hat Enterprise Linux 9 administration : a comprehensive Linux system administration guide for RHCSA certification exam candidates - Gómez, Pablo Iranzo; Requena, Pedro Ibáñez; Colino, Miguel Pérez; McCarty, Scott (Packt Publishing Ltd., 2022)
With Red Hat Enterprise Linux 9 becoming the standard for enterprise Linux used from data centers to the cloud, Linux administration skills are in high demand. With this book, you'll learn how to deploy, access, tweak, and improve enterprise services on any system on any cloud running Red Hat Enterprise Linux 9. Throughout the book, you'll get to grips with essential tasks such as configuring and maintaining systems, including software installation, updates, and core services. You'll also understand how to configure the local storage using partitions and logical volumes, as well as assign and deduplicate storage. You'll learn how to deploy systems while also making them secure and reliable. This book provides a base for users who plan to become full-time Linux system administrators by presenting key command-line concepts and enterprise-level tools, along with essential tools for handling files, directories, command-line environments, and documentation for creating simple shell scripts or running commands. With the help of command line examples and practical tips, you'll learn by doing and save yourself a lot of time. By the end of the book, you'll have gained the confidence to manage the filesystem, users, storage, network connectivity, security, and software in RHEL 9 systems on any footprint.